Where Does the Blood Come From?: True Stories and Real Selves at the TRC Hearings - Corry, Wendy; Terre Blanche, Martin (PINS-Psychology in Society, 2026)
While much of the academic work on the Truth and Reconciliation Commission (TRC) has been broadly constructionist in character, such work typically draws a line around the physical and historical reality of abuse. In this article we consider the key elements necessary to a thorough-going constructionist reading of TRC survivor narratives. Read from a top-down perspective, survivor narratives are the product of the legal, political, religious and media discourses that went into the making of the TRC. Read from a bottom-up perspective, survivor narratives involve the recursive construction of a self able to reflect on itself as the subject of a human rights abuse.